Imperfect Procedural Knowledge: Evidence from a Field Experiment to Encourage Water Conservation - Sebastian Tonke (ZBW - Leibniz Information Centre for Economics, 2020)
Individuals often desire to achieve certain outcomes, but potentially lack the procedural knowledge on how to do so. This study provides causal evidence that imperfect procedural knowledge is a severe obstacle to efficient behavior, but can be overcome by providing low-cost information. I conduct a large-scale field experiment with a public water utility to encourage water conservation during a drought. Providing mass-targeted conservation strategies via text message decreases consumption by 5.2 percent. Additional treatments encouraging individuals to develop own strategies are ineffective and rule out alternative explanations such as reminders, awareness of water scarcity, or being asked to reduce consumption.
Keywords: C93; D91; Q25; 330; Field experiment; information provision; resource conservation